2018
DOI: 10.1186/s12967-018-1637-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular network-based identification of competing endogenous RNAs and mRNA signatures that predict survival in prostate cancer

Abstract: BackgroundThe aim of the study is described the regulatory mechanisms and prognostic values of differentially expressed RNAs in prostate cancer and construct an mRNA signature that predicts survival.MethodsThe RNA profiles of 499 prostate cancer tissues and 52 non-prostate cancer tissues from TCGA were analyzed. The differential expression of RNAs was examined using the edgeR package. Survival was analyzed by Kaplan–Meier method. microRNA (miRNA), messenger RNA (mRNA), and long non-coding RNA (lncRNA) networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…Most lncRNAs and miRNAs may function as one member of the ceRNA regulatory networks. In fact, several reports have suggested that the ceRNA networks are related to the occurrence and progression of tumors, such as hepatocellular carcinoma [28], prostate cancer [29] and glioblastoma [30]. However, there have been few reports regarding the ceRNA regulatory networks and their involvement in drug resistance except for chemoesistance to osteosarcoma [23] and cisplatin-resistance to epithelial ovarian cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…Most lncRNAs and miRNAs may function as one member of the ceRNA regulatory networks. In fact, several reports have suggested that the ceRNA networks are related to the occurrence and progression of tumors, such as hepatocellular carcinoma [28], prostate cancer [29] and glioblastoma [30]. However, there have been few reports regarding the ceRNA regulatory networks and their involvement in drug resistance except for chemoesistance to osteosarcoma [23] and cisplatin-resistance to epithelial ovarian cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…These findings provided indirect evidence for the hypothesis that CYFIP2 participated in the pathogenic mechanism of BCC. HOXB5 is a member of the homeobox (HOX) gene B cluster and plays key roles in several cancers [30,31]. Lee et al suggested that HOXB5 increased cell proliferation and invasiveness in estrogen receptor-(ER-) positive breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that GPC2 could promote proliferation of neuroblastoma cells as a result of MYCN binding to a motif of the promoter of GPC2 and gain of chromosome 7q (37). GPC2 can also be used an effective prognostic indicator for prostate cancer and neuroblastoma (37)(38)(39). GPC3 inhibits cell cycle in renal cancer cells 786-O and ACHN at G1 phase (40).…”
Section: Discussionmentioning
confidence: 99%